Bronchoscopic lung volume reduction – current opinion (Swiss Medical Weekly, 2010)
Bronchoscopic lung volume reduction is a new technology designed to reduce hyperinflation in severe COPD by implantation of endobronchial devices, such as biodegradable material, endobronchial valves or bronchopulmonary stents, via flexible bronchoscopy. This article discusses newest developments and results in bronchoscopic lung volume reduction.